Strategi Pengembangan Wisata Kecamatan Dlingo Melalui Mobile Apps Dengan Memanfaatkan Sistem Informasi Geografis (SIG) - Kussujaniyatun, Sri; Probosari, Ninik; Hartati, Anis Siti (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
Tourism development is one of the efforts to explore the regional income ofBantul Regency. Dlingo district also offer various tourism sector even some local residents haven’t know yet the potential offered by Dlingo such as village tourism and natural attractions. The mapping of tourism locations in the Dlingo sub-district which will be carried out in the early stages of this research is based on mobile apps by utilizing a geographic information system (GIS), to be able to find out the types and potential of natural tourism both still in development stage and those that have not yet been developed. The purpose of this study is to map tourism potential using performance and need assessment as well as utilizing GIS. It is expected that with the mapping of tourism can determine the locations of tourist spots and make it easier for local and foreign tourists to choose the tourist attractions they want to visit. Besides that, the development of tourism potential will increase people's income and revenue. Data collection techniques used were questionnaires, interviews, documentation, field observations and data processing techniques of geographic information systems (GIS). The results of this study are in the form of an information system model for the promotion of Dlingo tourism in the form of Android and IOS applications named